Genetic association between different criteria to define sexual precocious heifers with growth, carcass, reproductive and feed efficiency indicator traits in Nellore cattle using genomic information - Bonamy, Martin; Kluska, Sabrina [UNESP]; Peripolli, Elisa [UNESP]; de Lemos, Marcos Vinícius Antunes [UNESP]; Amorim, Sabrina Thaise [UNESP]; Vaca, Roberto Jose; Lôbo, Raysildo Barbosa; de Castro, Letícia Mendes; de Faria, Carina Ubirajara; Borba Ferrari, Fabio [UNESP]; Baldi, Fernando [UNESP] (Wiley, 2019)
The aim of this study was to estimate genetic parameters for different precocious calving criteria and their relationship with reproductive, growth, carcass and feed efficiency in Nellore cattle using the single-step genomic BLUP. The reproductive traits used were probability of precocious calving (PPC) at 24 (PPC24), 26 (PPC26), 28 (PPC28) and 30 (PPC30) months of age, stayability (STAY) and scrotal circumference at 455 days of age (SC455). Growth traits such as weights at 240 (W240) and 455 (W455) days of age and adult weight (AW) were used. Rib eye area (REA), subcutaneous fat thickness (SFT), rump fat thickness (RFT) and residual feed intake (RFI) were included in the analyses. The estimation of genetic parameters was performed using a bi-trait threshold model including genomic information in a single-step approach. Heritability for PPC traits was moderate to high (0.29–0.56) with highest estimates for PPC24 (0.56) and PPC26 (0.50). Genetic correlation estimates between PPC and STAY weakened as a function of calving age. Correlation with SC455, growth and carcass traits were low (0.25–0.31; −0.22 to 0.04; −0.09 to 0.18, respectively), the same occurs with RFI (−0.09 to 0.08), this suggests independence between female sexual precocity and feed efficiency traits. The results of this study encourage the use of PPC traits in Nellore cattle because the selection for such trait would not have a negative impact on reproductive, growth, carcass and feed efficiency indicator traits. Stayability for sexual precocious heifers (PPC24 and PPC26) must be redefined to avoid incorrectly phenotype assignment.
Keywords: genetic correlations; genomic; Nellore; precocity; ssGBLUP